2005
DOI: 10.1038/sj.mp.4001628
|View full text |Cite
|
Sign up to set email alerts
|

Active zones for presynaptic plasticity in the brain

Abstract: Some of the most abundant synapses in the brain such as the synapses formed by the hippocampal mossy fibers, cerebellar parallel fibers and several types of cortical afferents express presynaptic forms of long-term potentiation (LTP), a putative cellular model for spatial, motor and fear learning. Those synapses often display presynaptic mechanisms of LTP induction, which are either NMDA receptor independent of dependent of presynaptic NMDA receptors. Recent investigations on the molecular mechanisms of neurot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 174 publications
(216 reference statements)
0
13
0
Order By: Relevance
“…Therefore, our results suggest that CAPS2 is critical for the enhancement of regulated BDNF secretion but that CAPS2 is not essential for regulated secretion. Recent studies have shown that CAPS promotes trans-soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) complex formation in DCV exocytosis (26), and an alternative pathway or proteins, such as mammalian homologue of C. elegans unc13-1 (Munc13-1) (27) and CAPS1 (4), could substitute for CAPS2 in CAPS2-KO neurons. In the latter study, CAPS2 was proposed to promote SV exocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our results suggest that CAPS2 is critical for the enhancement of regulated BDNF secretion but that CAPS2 is not essential for regulated secretion. Recent studies have shown that CAPS promotes trans-soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) complex formation in DCV exocytosis (26), and an alternative pathway or proteins, such as mammalian homologue of C. elegans unc13-1 (Munc13-1) (27) and CAPS1 (4), could substitute for CAPS2 in CAPS2-KO neurons. In the latter study, CAPS2 was proposed to promote SV exocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of 14-3-3 proteins with RIMs is regulated by the phosphorylation status of RIMs as only RIM that is phosphorylated at serine 413 binds to 14-3-3 proteins (Lonart et al 2003). RIM mutants have been analyzed in C. elegans (Koushika et al 2001) and in mice in which RIM1α knockouts have been studied in great detail (for reviews, see Garcia-Junco-Clemente et al 2005;Kaeser and Sudhof 2005). UNC-10 mutants of C. elegans exhibit a five-fold reduction in fusion-competent vesicles at release sites (Koushika et al 2001).…”
Section: -3-3 (Simsek-duran Et Al 2004)mentioning
confidence: 99%
“…However, zinc, copper and magnesium have been reported to block the channel and causing antagonistic effects (Eby and Eby, 2006; Gass and Olive, 2008; Huggins and Grant, 2005; Rambo et al, 2012; Trombley et al, 1998). These receptors have been mostly found on presynaptic nerve-terminals and glial cells (Garcia-Junco-Clemente et al, 2005; Paoletti and Neyton, 2007), with an implication in neural plasticity (Coyle and Tsai, 2004; Malenka and Nicoll, 1993; Paoletti et al, 2013). …”
Section: Glutamate Receptors In Audmentioning
confidence: 99%